ChemInform Abstract: Polystyrene Copolymer Supported by Substituted (1R, 2R)‐1, 2‐Diphenylethane‐1, 2‐diamine‐copper(II) Complexes: A Recyclable Catalyst for Asymmetric Henry Reactions. Issue 42 (14th October 2014) - Androvic, Ladislav; Drabina, Pavel; Panov, Illia; Frumarova, Bozena; Kalendova, Andrea; Sedlak, Milos
Abstract The title catalyst is employed for the reactions of functionalized aldehydes with nitromethane to give 2‐nitroethanols in excellent yields and high enantioselectivities.